KEBIJAKAN FORMULASI TINDAK PIDANA DEEPFAKE DALAM UNDANG-UNDANG INFORMASI DAN TRANSAKSI ELEKTRONIK (UU ITE) DAN UNDANG-UNDANG PELINDUNGAN DATA PRIBADI (UU PDP) DI INDONESIA - Nurul Aulia Fitriani; Endik Wahyudi (Fakultas Hukum Universitas Kristen Indonesia, 2026)
The development of deepfake technology derived from intelligent computational systems poses a new threat in cybercrime through the manipulation of digital identities whose characteristics closely resemble genuine materials. This study examines the policy formulation of deepfake criminal acts in the current and future Indonesian ITE Law and PDP Law. The research uses the legal protection theory from Philipus M. Hadjon and the criminal law policy theory from Barda Nawawi Arief, with a doctrinal legal analysis emphasizing legislative instruments The results show that the current policy formulation is still implicit and partial, where Article 27 of the ITE Law and Article 65 of the PDP Law can be applied but do not explicitly regulate deepfake as a distinct offense, causing difficulties in evidence and coordination obstacles between institutions. The study concludes that a reformulation is needed through the formulation of a specific deepfake crime with comprehensive elements, adopting the practices of South Korea and China to provide legal certainty and effective victim protection.